Structural and electrical properties of (PbSe)1·16TiSe2. Issue 6 (1st November 2012) - Disch, Sabrina; Atkins, Ryan; Johnson, David C.; Jones, Zachary; Stolt, Matthew J.; Sitts, Luke; Moore, Daniel B.; Beekman Matt, Matt Beekman
Abstract : The synthesis and characterization of a new layered compound with the composition (PbSe)1·16 TiSe2 in thin-film form is reported in this study. The structure of the new compound was characterized by specular and in‐plane synchrotron x‐ray diffraction studies, which indicate that the compound can be described as a layered intergrowth of PbSe and TiSe2 in which the individual constituents are precisely layered yet rotationally (turbostratically) disordered with an average in‐plane domain size in the order of 10 nm. In contrast to crystalline (PbSe)1·16 (TiSe2 )2 prepared by solid‐state reaction at high temperature, the electrical resistivity in the range 20–300 K is nearly temperature independent. The Seebeck coefficient at room temperature was measured to be S = –66(1) μV/K at the carrier concentration of n = 2·1(5) × 10 21 cm ‐3, indicating behavior characteristic of a heavily doped semiconductor. The electrical transport properties for the (PbSe)1·16 TiSe2 compound are compared and contrasted to those of other misfit‐layered and turbostratically disordered (MX)1+δ (TX2 ) n compounds. The synthesis and characterization of a new layered compound with the composition (PbSe)1·16 TiSe2 in thin-film form is reported in this study. The structure of the new compound was characterized by specular and in-plane synchrotron x-ray diffraction studies, which indicate that the compound can be described as a layered intergrowth of PbSe and TiSe2 in which the individual constituents are precisely layered yet rotationally (turbostratically) disordered with an average in-plane domain size in the order of 10 nm. In contrast to crystalline (PbSe)1·16 (TiSe2 )2 prepared by solid-state reaction at high temperature, the electrical resistivity in the range 20–300 K is nearly temperature independent. The Seebeck coefficient at room temperature was measured to be S = −66(1) μV/K at the carrier concentration of n = 2·1(5) × 10 21 cm −3, indicating behavior characteristic of a heavily doped semiconductor. The electrical transport properties for the (PbSe)1·16 TiSe2 compound are compared and contrasted to those of other misfi t-layered and turbostratically disordered (MX)1+δ (TX2 )n compounds.